Evaluation of the Effectiveness of Silver Diamine Fluoride in Arresting Caries in Primary Teeth - Nishita Garg; Sayani Roy; Abhay Kumar Jain; Tapan Kumar Mandal; M S Girish; Parul Priya (Journal of Pharmacy and Bioallied Sciences)
Background: Silver diamine fluoride (SDF) has been identified as a noninvasive way to stop dental caries from becoming worse, particularly in baby teeth. Materials and Methods: A hundred kids between the ages of 3 and 6 who have at least one carious lesion in their primary teeth participated in a randomized controlled experiment. One of the two groups—the experimental group (n = 50), which got a 38% SDF therapy, or the control group (n = 50), which received a placebo—was randomly allocated to the subjects. Over the course of a year, the carious lesions received biannual applications of the SDF. The main result was the stoppage of caries, ascertained by monitoring the change of an active lesion to an inactive one using standardized digital radiographs and clinical evaluations. Results: Only 35% of the carious lesions in the control group showed evidence of arrest after a year, compared to 87% of lesions in the experimental group (P < 0.001). It was shown that there would be one carious lesion arrested for every 2.5 patients with SDF if the number required to treat (NNT) was 2.5. During the research, no notable side effects were noted. Conclusion: The remarkable efficacy of SDF in halting dental caries in primary teeth highlights its significance in the treatment of young dental patients.